2018
DOI: 10.1371/journal.pone.0207953
|View full text |Cite
|
Sign up to set email alerts
|

HIV-positive gay men’s knowledge and perceptions of Human Papillomavirus (HPV) and HPV vaccination: A qualitative study

Abstract: The human papillomavirus (HPV) is the most common sexually transmitted infection worldwide. Gay, bisexual, and other men who have sex with men (GBM) living with HIV are disproportionately impacted by HPV-associated anal cancer, with rates about 100-fold that of the general population. Fortunately, HPV vaccination has proven efficacy in preventing both anogenital warts (condyloma) in males and anal pre-cancers (anal intraepithelial neoplasia; AIN) in GBM up to the age of 26. We conducted in-depth, semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 33 publications
(36 reference statements)
1
44
1
Order By: Relevance
“…In addition to interviews with 25 GBM-LHIV patient-participants in Toronto, Canada, who had received anal cancer screening through HPV-SAVE, we interviewed 15 health service providers in Toronto, Ottawa and Vancouver, Canada. In this article, we focus on the data collected with providers to build upon recently published analyses of patients’ accounts of anal cancer screening [28] and HPV vaccination practices [16].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to interviews with 25 GBM-LHIV patient-participants in Toronto, Canada, who had received anal cancer screening through HPV-SAVE, we interviewed 15 health service providers in Toronto, Ottawa and Vancouver, Canada. In this article, we focus on the data collected with providers to build upon recently published analyses of patients’ accounts of anal cancer screening [28] and HPV vaccination practices [16].…”
Section: Methodsmentioning
confidence: 99%
“…Though these existing guidelines make recommendations about who should be vaccinated, in many contexts this guidance does not directly translate into what is actually made available via public programs. For example, in Canada, since 2016 most provincial insurance programs cover HPV vaccination for men who have sex with men only up to the age of 26 [16]. Otherwise, the vaccine cost ranges from $420 CAD (Gardasil-4) to over $560 CAD (Gardasil-9) for all three doses, which can be paid for with private health insurance for those who have adequate coverage, or out of pocket for those who are able to afford the costs [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Grace et al . ). From a prevention perspective, studies have confirmed that HIV‐positive persons who have achieved an undetectable viral load or ‘undetectability' (i.e.…”
Section: Gbm Mental Health and Hivmentioning
confidence: 97%